2019
DOI: 10.1007/s11104-019-04043-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term field study on stabilization of contaminated wastes by growing clonally reproduced Silene vulgaris calamine ecotype

Abstract: Aims Pseudo-metallophyte Silene vulgaris frequently colonizes polluted areas. We investigated whether plants obtained under in vitro conditions can be used to form long-term communities on zinc-lead tailings rich in cadmium. To this end, we checked the species stabilization capacity and biochemical properties of the area subjected to long-term cultivation of a local S vulgaris ecotype. We focused on evaluation of its ability to accumulate trace metals (TMs) after 10-year cultivation period. Methods The calamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Such conspicuous ambiguity of HMs categorization has led to general confusion regarding the significance of this term that has been recently subjected to a broad discussion. As a result of this consideration, the use of ‘trace element’ rather than ‘heavy metal’ seems to be more justified [14,15,16]. The present review fits well to this novel approach, since it is mostly focused on the profitable impact of the so-called HMs on plant organism.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Such conspicuous ambiguity of HMs categorization has led to general confusion regarding the significance of this term that has been recently subjected to a broad discussion. As a result of this consideration, the use of ‘trace element’ rather than ‘heavy metal’ seems to be more justified [14,15,16]. The present review fits well to this novel approach, since it is mostly focused on the profitable impact of the so-called HMs on plant organism.…”
Section: Introductionmentioning
confidence: 81%
“…However, it should not be forgotten that, despite many processes that regulate ions accumulation and transport in plants, when metal concentrations in the environment reach the critical level, the control mechanisms that are responsible for ion homeostasis in the protoplast may break down and the unrestricted influx of cations occurs. Among the plants colonizing highly polluted with heavy metals post-industrial waste heaps, excluder behaviour has been observed in specimens from metalliferous populations of Alyssum montanum [90] (Figure 4A), Dianthus carthusianorum [146] (Figure 4B), Potentilla arenaria [147] (Figure 4C), Scabiosa ochroleuca [147,148] (Figure 4D), or Silene vulgaris [16] (Figure 4E).…”
Section: Metallophytes As Unique Communities From Metalliferous Sitesmentioning
confidence: 99%
“…Recently, the potential of native metal-tolerant species for revegetation has been successfully verified for Agropyron smithii and Artemisia tridentate [ 51 ], Lygeum spartum [ 52 ], Achillea wilhelmsii [ 53 ], and Matthiola dagestanica and Draba stylaris [ 46 ]. The usefulness of metallophytes for revegetation and the phytostabilization of Zn-Pb rich soils in the Olkusz Ore-bearing Region, one of the biggest industrial areas in Poland, has been also proven in our earlier studies for Biscutella laevigata [ 49 , 54 ], Dianthus carthusianorum [ 49 ], Gypsophila fastigiata [ 55 ], and Silene vulgaris [ 56 ]. Undoubtedly, phytoremediation combined with the biological reclamation of destroyed or degraded ecosystems may constitute a new and safe opportunity for humans to positively interact with the environment.…”
Section: Functional Traits Of Plants Developed In Response To Severe ...mentioning
confidence: 92%
“…Micropropagation techniques enable faster production of vegetative offspring in comparison with classic reproduction methods (Hanus-Fajerska et al 2019;Muszyńska et al 2018;Philips and Garda 2019). Culturing tissues and organs in vitro allows regenerating numerous micro-plantlets, from single donor plant or from its fragments.…”
Section: Introductionmentioning
confidence: 99%